Paclitaxel and Carboplatin in Patients With Completely or Optimally Resected Carcinosarcoma of the Uterus: A Phase II Trial by the Japanese Uterine Sarcoma Group and the Tohoku Gynecologic Cancer Unit. Issue 1 (1st January 2015) - Otsuki, Ai; Watanabe, Yoh; Nomura, Hiroyuki; Futagami, Masayuki; Yokoyama, Yoshihito; Shibata, Kiyosumi; Kamoi, Seiryu; Arakawa, Atsushi; Nishiyama, Hiroshi; Katsuta, Takahiro; Kudaka, Wataru; Shimada, Muneaki; et al.
Abstract : Objective: This study aimed to evaluate the efficacy of paclitaxel and carboplatin in patients with completely or optimally resected uterine carcinosarcoma. Materials and Methods: We conducted a single-arm multicenter prospective phase II trial at 20 Japanese medical facilities. Eligible patients had histologically confirmed uterine carcinosarcoma without prior chemotherapy or radiotherapy. Patients received 6 courses of 175 mg/m 2 paclitaxel over 3 hours, followed by a 30-minute intravenous administration of carboplatin at an area under the serum concentration-time curve of 6. Results: A total of 51 patients were enrolled in this study, 48 of whom underwent complete resection and 3 of whom underwent optimal resection. At 2 years, the progression-free survival and overall survival rates were 78.2% (95% confidence interval [CI], 64.1%–87.3%) and 87.9% (95% CI, 75.1%–94.4%), respectively. At 4 years, these rates were 67.9% (95% CI, 53.0%–79.0%) and 76.0% (95% CI, 60.5%–86.1%), respectively. Although 15 patients showed disease recurrence during the follow-up period (median, 47.8 months; range, 2.1–72.8 months), a total of 40 (78.4%) patients completed the 6 courses of treatment that had been planned. Conclusions: The combination of paclitaxel and carboplatin was a feasible and effective postoperative adjuvant therapy for patients with completely or optimally resected uterine carcinosarcoma.